Myocarditis Caused by Brucella melitensis in the Absence of Endocarditis: Case Report and Review of the Literature - Maria Lagadinou; Virginia Mplani; Dimitrios Velissaris; Periklis Davlouros; Markos Marangos (Case Reports in Medicine)
Brucellosis remains an important public health problem with endemic characteristics in many countries. Brucellosis can affect almost all organs and systems of human body. Cardiac complications are unusual, occurring in less than 2% of patients and usually manifest as endocarditis. We present the case of a 21-year-old Caucasian man, who was admitted to the University Hospital of Patras, Western Greece, with fatigue, fever up to 39°C, and retrosternal pain. Musculoskeletal, genitourinary, gastrointestinal, hematologic, nervous, skin, and mucous membranes and respiratory complications have been reported in several cases of brucellosis. Development of myocarditis is a highly rare complication of brucellosis, particularly in the absence of concomitant endocarditis. Clinicians should be aware of this clinical entity especially in endemic areas as appropriate antibiotic treatment is life-saving and may prevent serious cardiologic disorders.